2021
DOI: 10.1111/febs.15750
|View full text |Cite
|
Sign up to set email alerts
|

Clinical advances in targeting epigenetics for cancer therapy

Abstract: The appropriate coordination between epigenetic regulators is essential for spatial and temporal regulation of gene expression and maintenance of cell identity. Cancer is a disease driven by both genetic and epigenetic alterations. The widespread dysregulation and reversible nature of epigenetic alterations confer cancer cells with vulnerabilities for therapeutic interventions. Over the past decades, remarkable progress has been made in developing drugs that target epigenetic regulators, with many drugs under … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
63
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(63 citation statements)
references
References 189 publications
(235 reference statements)
0
63
0
Order By: Relevance
“…Indeed, a recent study showed an imbalance in ADAR1 and ADAR2 enzyme expression in HB tumors, accompanied by global RNA hypoediting. However, the authors also reported specific hyperediting of the BLCAP transcript, which is a highly conserved gene with tumor suppressor activities [18,217] . Despite the fact that this field requires deeper understanding, the study of this new epigenetic mechanism could contribute to the understanding of HB development and the design of novel "epidrugs" for the treatment of this and other tumors.…”
Section: Rna Editingmentioning
confidence: 98%
“…Indeed, a recent study showed an imbalance in ADAR1 and ADAR2 enzyme expression in HB tumors, accompanied by global RNA hypoediting. However, the authors also reported specific hyperediting of the BLCAP transcript, which is a highly conserved gene with tumor suppressor activities [18,217] . Despite the fact that this field requires deeper understanding, the study of this new epigenetic mechanism could contribute to the understanding of HB development and the design of novel "epidrugs" for the treatment of this and other tumors.…”
Section: Rna Editingmentioning
confidence: 98%
“…Both these modifications serve as molecular markers for “reader” proteins which subsequently recruit chromatin remodelers and non‐coding RNA to transduce downstream signaling mechanisms. These chemical modifications can also be reversed by “erasers” [106] . Dysregulation of these epigenetic processes is now recognized as a universal feature of cancers, with genome‐wide alterations in epigenetic profiles frequently detected in adult and pediatric cancers, as is the genetic mutation of “writer”, “readers” and “erasers”.…”
Section: Epigeneticsmentioning
confidence: 99%
“…Dysregulation of these epigenetic processes is now recognized as a universal feature of cancers, with genome‐wide alterations in epigenetic profiles frequently detected in adult and pediatric cancers, as is the genetic mutation of “writer”, “readers” and “erasers”. However, due to the reversible nature of epigenetic modification, targeted agents against these processes are being widely investigated [106] …”
Section: Epigeneticsmentioning
confidence: 99%
“…Inhibiting DNA methyltransferases (DNMTs) may avoid hypermethylation of CDH1 and tumor suppressors, while the inhibitory chromatin-modifying effects of EZH2 may represses PRC2 activity. The blocking of histone deacetylases (HDACs) may prevent histone modifications implicated in cancer [ 101 , 102 ]. Targeting epigenetic- and chromatin-related EMT processes in combination with standard therapeutic approaches such as ADT should be a promising strategy for improving disease outcome in PCa.…”
Section: Clinical Trialsmentioning
confidence: 99%